Ablation of Tacr2 in mice leads to gastric emptying disturbance. Issue 11 (6th June 2017) - Mao, Y.‐L.; Shen, C.‐L.; Zhou, T.; Ma, B.‐T.; Tang, L.‐Y.; Wu, W.‐T.; Zhang, H.‐X.; Lu, H.‐L.; Xu, W.‐X.; Wang, Z.‐G.
Abstract: Background: Tacr2 is one of the G protein‐coupled receptors(GPCRs) that mediate the biological actions of tachykinins. It is abundantly expressed in the gastrointestinal (GI) system and is thought to play an important role in GI motility, secretion, and visceral sensitivity. Previously, the physiological and pathophysiological functions of Tacr2 were mainly studied using Tacr2 selective agonists or antagonists. Here, we seek to investigate the effect of Tacr2 disruption in mice to provide further insights. Methods: The Tacr2 knockout mice were generated by homologous recombination and the phenotypic changes of the Tacr2 ‐null mice were analyzed and compared with their wild type (wt) littermates. Key Results: Increased food retention was detected in Tacr2 −/− mice. The stomach of Tacr2 −/− mice had thinner muscularis externa and less neurons in the myenteric plexus. The stomach and small intestine exhibited longer duration of electrical field stimulation (EFS)‐induced inhibition in the gastric fundus and decreased frequency of migrating motor complex (MMC), respectively. Neuronal nitric oxide synthase (nNOS) and vasoactive intestinal polypeptide (VIP) were significantly up‐regulated due to Tarc2 deficiency, contributing to enhanced nitric oxide (NO) signaling in the stomach of Tacr2 −/− mice. Intraperitoneal application of 7‐nitroindazole (7‐NI) to Tacr2 −/− mice effectively relieved the gastric emptying disturbance. Moreover, Creb and NF‐κB signalings were involved in the regulation of these physiological changes initiated by Tacr2 deficiency. Conclusions & Inferences: Tacr2 negatively regulated the expression of nNOS and VIP both in vivo and in vitro. Its ablation in mice elevated the expression of nNOS and VIP, enhanced NO signaling and changed the Creb and NF‐κB signalings, finally leading to the gastric emptying disturbance of Tacr2 −/− mice. Abstract : Tacr2 deficiency in mice increased food retention in stomach, which exhibited thinner muscularis externa, less neurons in the myenteric plexus, longer duration of EFS‐induced inhibition in gastric fundus and decreased frequency of migrating motor complex (MMC) in the small intestine. nNOS and VIP expression, negatively regulated by Tacr2 in vitro, was up‐regulated in the stomach of Tacr2 −/− mice. Elevated nNOS expression caused enhanced NO signaling, contributing to the gastric emptying disturbance in Tacr2 −/− mice, which could be rescued by treatment with 7‐NI, a selective nNOS inhibitor.